Synthesis and Characterization of Porous Fly Ash-Based Geopolymers Using Si as Foaming Agent - D. Kioupis; Ch. Kavakakis; S. Tsivilis; G. Kakali (Advances in Materials Science and Engineering)
This paper concerns the synthesis of foamed geopolymers using fly ash and metallic Si as the binder and the porogent agent, respectively. The Taguchi approach was applied in order to study the effect of some significant synthesis parameters such as the Si foaming agent content (% w/w fly ash based), the alkali type (R : Na or K), and the alkalinity (R/Al molar ratio) of the activation solution on the compressive strength and apparent density of the foamed geopolymers. The final products were characterized by means of XRD, FTIR, and SEM, while optical microscopy was applied for the evaluation of the porosity. Lightweight geopolymers with a compressive strength of 2.08–14.88 ΜPa and an apparent density of 0.84–1.55 g/cm3 were prepared by introducing a Si content up to 0.2% w/w on fly ash basis.